Suitability assessments in teacher education during and post the COVID-19 pandemic – an impact on professional development - Hvalby, Mette (Frontiers in Education, 2023)
Suitability assessment of Norwegian pre-service teachers is carried out by teacher educators, and the mentors' professional practices play a key role in these processes. This study aims to explore how the Covid-19 pandemic has influenced suitability assessment practices of preservice teachers. The purpose of the suitability assessment is to ensure that vulnerable groups, such as students in schools, encounter teachers who are suitable for a professional practice.The process of growing suitability includes professional development, while suitability assessment of pre-service teachers intends to strengthen the quality of teacher education programs. Two sets of data collection methods are underpinning the arguments in this qualitative study. Data were collected in 2022 from a survey with a sample of 162 mentors in teacher education attending three universities. Thereafter, in-depth interviews were conducted with three Heads of suitability assessment from the same universities as the mentors. The triangulation aimed to reduce bias and increase the validity. The impact the pandemic has had on the suitability assessment practices is expressed in four findings: 1) a weaker basis for the assessment, 2) continuing health issues, 3) delayed professional development among preservice teachers, and 4) differences among the universities. Implications for education programs for mentoring including knowledge of the procedures of suitability assessments, and a closer collaboration between all teacher educators involving systematically evaluation of pre-service teachers are indicated for future teacher education.